Asthma mortality in Birmingham 1975-7: 53 deaths. Issue 6215 (8th March 1980) - Ormerod, L P; Stableforth, D E
Abstract : Out of 83 patients studied 72 were certified as dying from asthma, and 11 aged under 45 as dying from chronic bronchitis and pneumonia. Fifty-three deaths were thought to be due to asthma. There were avoidable factors associated with several of these deaths from asthma. Recent discharge from hospital (16%), non-availability of aerosol bronchodilators (45%), underuse of corticosteroids (66%), and lack of objective measurements of airflow obstruction (100%) were found in deaths outside hospital. Inadequate initial assessment including baseline spirometry and blood gases (50%), significant underusage of corticosteroids (93%) and intravenous and nebulised bronchodilators (100%), and failure to monitor treatment objectively (100%) were found in deaths in hospital. "False-positive" and "false-negative" certifications of asthma were studied, and the findings suggest that these may lead to appreciable inaccuracy in the reporting of deaths from asthma.